Current Situation and Recommendations for Promoting Employee Commendation in Enterprises in Vietnam - Thuy, Pham Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
Human resource development plays a key role for every business. In human resource attraction and development policies, commendation is regarded by enterprises as an effective measure for encouraging employees to dedicate themselves to work. This paper analyzes the significance and practices of commendation in Vietnamese enterprises, and then proposes some solutions for the enterprises to strengthen commendation for employees.